2001
DOI: 10.1046/j.1365-3156.2001.00685.x
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Schistosoma mansoni infection in a rural area in Brazil. II: Household risk factors

Abstract: SummaryA number of studies have pointed out the potential importance of the household in the transmission of schistosomiasis. The clustering of domestic activities associated with water collection, storage, and usage can result in the sharing of transmission sites and infective water contact behaviours. In this study, we employed a variance component method to estimate effects due to individual risk factors and shared residence on the variance in faecal egg counts during Schistosoma mansoni infection. A suite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
70
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 42 publications
3
70
0
Order By: Relevance
“…The influence of education, occupation and religion on schistosomiasis in pregnant women is similar to that of the general population. A poor level of education appears to be a risk factor for urogenital schistosomiasis in Nigeria in present study, intestinal schistosomiasis in Brazil (Bethony et al 2001) and many other parasitic diseases throughout the developing world (Montresor et al 2001;Asaolu and Ofoezie 2003;Stothard et al 2006;Aagaard-Hansen et al 2009). This association is probably multi-faceted, education affecting attitudes and behavior in different ways in different settings (Ugbomoiko et al 2010).…”
Section: Discussionmentioning
confidence: 50%
“…The influence of education, occupation and religion on schistosomiasis in pregnant women is similar to that of the general population. A poor level of education appears to be a risk factor for urogenital schistosomiasis in Nigeria in present study, intestinal schistosomiasis in Brazil (Bethony et al 2001) and many other parasitic diseases throughout the developing world (Montresor et al 2001;Asaolu and Ofoezie 2003;Stothard et al 2006;Aagaard-Hansen et al 2009). This association is probably multi-faceted, education affecting attitudes and behavior in different ways in different settings (Ugbomoiko et al 2010).…”
Section: Discussionmentioning
confidence: 50%
“…[10][11][12] The clustering of domestic activities associated with water collection, storage, and usage can lead to the sharing of infective sites and infective water contact behaviors, exposing household members to similar risks of infection. 13 In our previous study, 7 we determined that shared residence accounted for 28% of the variance in fecal egg counts. When covariates, such as gender, water contact behavior, occupation, and income, were included shared residence still accounted for 23% of the variation in fecal egg counts.…”
Section: Introductionmentioning
confidence: 99%
“…Marked variation in egg counts have also been observed between individuals within single communities. [6][7][8] An important implication of the overdistribution in egg counts is that the majority of eggs excreted in a community come from a minority of residents. For example, a study of S. haematobium in Ethiopia found that 50% of the eggs were excreted by 5% of the community.…”
Section: Introductionmentioning
confidence: 99%
“…105(4): 570-577, July 2010 There is much scientific evidence that socio-demographic variables and contact with unsafe water are associated with infection with schistosomiasis. Studies in different settings have been carried out describing vulnerable parts of the population, such as school children, types of behaviour related to a higher risk of acquiring the infection, as is the case with household, occupational and leisure activities, or involving socio-economical status and its correlation to the disease (Lima e Costa 1983, Guimarães et al 1985, Cairncross et al 1996, da Silva et al 1997, Moza et al 1998, Watts et al 1998, Bethony et al 2001, Massara et al 2004, Gazzinelli et al 2006. Studies carried out in Africa investigating infections with Schistosoma haematobium present similar associations, demonstrating the importance of studies involving snail hosts, water contacts and micro-spatial distribution for an integrated epidemiological approach (Stothard et al 2002).…”
mentioning
confidence: 99%